Ks. Jan Doppke, Katechizacja w Polsce 1945-1990, Wydawnictwo Bernardinum, Pelplin 1998, ss. 248 - Głowacka, Edyta (Biuletyn Historii Wychowania, 2000)
Ks. Jan Doppke, Katechizacja w Polsce 1945-1990, Wydawnictwo Bernardinum, Pelplin 1998, ss. 248